Pyxista: Snake & Ladder Board Game - Khairunnisa Asman; Nurul Alisha Umaira Mohd Fadli; Nurul Fatiha Abdul Rahman; Shafinah Kamarudin; Nurhidaya Mohamad Jan; Siti Munirah Mohd (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan